Analysis Of The Effect Telephone Counseling By Nurses On The Compliance Of The Control Of DOTS Poly Tuberculosis Patients at Dungus Madiun Lung Hospital - Winarto, Agus; Bintoro, Tjahja (Journal Of Nursing Practice, 2018)
Background: Adherence to treatment is the behavior of TB patients to come control in accordance with control schedule in DOTS Poly Dungus Madiun Lung Hospital. Telephone counseling is a communication performed by nurse DOTS Poly Dungus Madiun Lung Hospital to the TB patient or his family using a telephone, with the intention of asking about the state of his illness, current complaints, motivate regularly taking medication, answer patient questions and complaints, and reminded drug taking schedule. Purpose : The purpose of this study is to prove the influence of the provision of telephone counseling by nurses to the compliance of TB DOTS patient control in Dungus Madiun Lung Hospital. Methods : Research design Pre- Experiment with a one-shot case study design. The population is TB Patients treated in poly DOTS from January 2017 to March 2017 with a sample of 15 respondents by purposive sampling. Data collection using a checklist of telephone counseling and checklist the observation of the arrival of the control on time after given counseling via telephone,checklist data was analyzed with Binomial Test. Result : Research result, after counseling via telephone almost all respondents came to the control on time 13 respondents (87%) and there is the effect of telephone counseling by nurses on the compliance of the control of DOTS poly tuberculosis patients at Dungus Madiun Lung Hospital. (Binomial with sig = 0.007 <Î± = 0.05 then H0 is rejected). Conclusion : Provision of counseling is necessary to improve patient compliance in treatment until completion. With telephone counseling from TB DOTS poly nurse to patient, in addition to more effective communication awakening, as well as motivating patients to adhere to TB treatment programs